(untitled) (Journal of Cancer Research Updates, 2013)
Protein kinaseshave become the second most important group of drug targets, after G-protein-coupled receptors. Currently,15 small molecule protein kinase inhibitors (PKIs) have received food and drug administrator (FDA) approval to be used as cancer treatments. However, in the course of clinical use of these small molecule PKIs, drug resistance has become a recurring problem. Their therapeutic potential depends on access to their intracellular targets, which significantly affected by certain membrane ATP-binding cassette(ABC) transporters. ABC transporters were major causesof clinical multiple drug resistance (MDR) and might be resulting in the development of resistance to PKIs in cancer patients. Some PKIs could modulate the activity of ABC transporters and affect the metabolism of themselves and other chemically unrelated drugs. Moreover, it has been recently reported that some PKIs could regulate the expression of ABC transporters in tumor cells, thereby affect their intracellular accumulation and antitumor efficacy. In this review,the reciprocal interaction of clinically important PKIs with the MDR-related ABC transporters, in particular ABCB1 and ABCG2,wassummarized. Keyword:Protein Kinase Inhibitors, ABC Transporters, P-gp/ABCB1, BCRP/ABCG2, Targeted Cancer Therapy.